Rethinking Social Security in Nigeria - Arum , Ifeyinwa; Likinyo, Olufunmi Solomon (Kashere Journal of Politics and International Relations, 2024)
Nigerians are disproportionately represented in the informal sector which comprises of small scale unregistered enterprises and people under informal employments. Many people in the informal sector earn very meager income, lack the privilege for human capital development, face exclusion and represent one of the weakest groups in the economy. Yet, social security schemes or programmes do not target them or focus more on people working in the formal sector through contributory pension schemes. There have been many intervention schemes undertaken by different Nigerian Governments that specifically targeted those outside formal employments. This paper will review and assess the attempts by the Nigerian Government to extend social security policies to people outside formal employments. The study also discusses the challenges encountered by these policies because it seems not to have effectively achieved its objectives. The secondary means of data collection was explored. The study recommends that Government should adopt a bottom up approach while designing these programmes. Stiff penalties should be meted out to corrupt Government officials who are found, trying to sabotage Governments efforts towards empowerment of the poor and vulnerable.